161k views
5 votes
Simplify the expression
9− 3(2)2

User Kosmos
by
5.0k points

2 Answers

3 votes

Answer:

- 3

Explanation:

These are the steps that I used are:

First, use PEMDAS.

Multiply and divide left to right.


3\left(2\right)\cdot \:2


3\left(2\right)=6


=6\cdot \:2 = 12.


= 9-12

Second, add and subtract, (left to right).


9-12=-3

= - 3.

So, 9 - 3(2)2 = -3.

User Girdeux
by
4.7k points
4 votes

Answer:

-3

Explanation:

9-3(2)2

9-(6)2

9-12

-3

User Icchanobot
by
5.4k points